The social significance of subtle signals. (July 2018) - Bliege Bird, Rebecca; Ready, Elspeth; Power, Eleanor
Abstract Acts of prosociality, such as donating to charity, are often analysed in a similar way to acts of conspicuous advertising; both involve costly signals revealing hidden qualities that increase the signaller's prestige. However, experimental work suggests that grand gestures, even if prosocial, may damage one's reputation for trustworthiness and cooperativeness if they are perceived as prestige enhancing: individuals may gain some types of cooperative benefits only when they perform prosocial acts in particular ways. Here, we contrast subtle, less obviously costly, interpersonal forms of prosocial behaviour with high-cost displays to a large audience, drawing on the example of food sharing in subsistence economies. This contrast highlights how highly visible prosocial displays may be effective for attracting new partners, while subtle signals may be crucial for ensuring trust and commitment with long-term partners. Subtle dyadic signals may be key to understanding the long-term maintenance of interpersonal networks that function to reduce unanticipated risks. Studying subtle signals of generosity is important to understand the long term maintenance of human cooperative networks. Certain types of low-cost food sharing among Martu women, for example, may signal commitment and cement cooperative ties.